A hydrocarbon pipeline spill risk assessment framework for drinking water supply. Issue 4 (15th July 2020) - Kammoun, Raja; Barrette, Simon; Bichai, Françoise; Dorner, Sarah; Prévost, Michèle
Abstract: Although infrequent, pipeline spills have the potential to contaminate source water supplies and disrupt drinking water production for extended periods. Detailed multiphase contaminant fate and transport models linked to hydrodynamic models are ideal for determining the potential impact of oil spills on drinking water sources. However, sufficient data are often unavailable to simulate spills scenarios. Thus, a simple semiquantitative modeling approach is proposed that is based on documented pipeline spills recorded in scientific literature. A risk matrix was used to combine the consequences of a spill with the probability that it would contaminate drinking water sources. The new Pipeline Spill Risk Assessment Framework was applied to 26 drinking water intakes located in the greater Montreal area (Quebec). The proposed framework allows for transparency and facilitation of public discussions with regard to oil spill risks and decision‐making for source water protection and water safety plans.